南極やまと山脈地域の氷中にサウスサンドイッチ諸島（Thule島、Zavodovski島）起源の火山灰を確認 - 大久保, 悠花; 福岡, 孝昭; 西尾, 文彦; Yuka, Okubo; Takaaki, Fukuoka; Fumihiko, Nishio (2013)
There are many tephra layers in the bare ice area near the Yamato Mountains, Antarctica. So far, 25 tephra samples were collected from ice sheets in the Yamato Mountains area, Antarctica. They were classified to 13 types from their chemical composition. Volcanoes of the South Sandwich Islands are candidate as the source for the tephras base on the tholeiitic chemical compositions and wind direction. We analyzed the major and rare earth element compositions of groundmass samples purified from volcanic rocks such as scoria and lava collected from Thule and Zavodovski islands, the South Sandwich Islands. Major and rare earth element compositions for those samples belong to tholeiite series. The chemical composition for one of Thule island samples agree well with those for tephra Belgica-IA tephra in ice sheet in the Yamato Mountains. Also the chemical compositions for one of Zavodovski samples agree well with those of RY80 tephra. So, we found tephras originated from Thule and Zavodovski islands, the South Sandwich Islands in ice sheet near the Yamato Mountains, Antarctica. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月15日（金） 統計数理研究所 ３階セミナー室１（D305） conference object